Complications of the suburethral sling in the form of Mini Vaginal Tape (MVT): A case report. (April 2022) - Islam, Md. Mominul; Islam, Md. Saiful; Alam, A.K.M. Khurshidul; Hallaz, Mohammad Monsur
Abstract: Synthetic sub-urethral sling has become the most widely used technique for the surgical management of stress urinary incontinence. Despite a higher success rate, complications like migration, encrustation, and stone formation have been reported by a mid-urethral sling (MUS). Among mid-urethral sling procedures, mini vaginal tape (MVT) is very popular. As periurethral stone formation and urethrovaginal fistula are very uncommon after MVT, case report on this issue is sparse. The current case report features a 55-year female presented with lower abdominal pain and continuous urinary incontinence, 10 years after the MVT. She was diagnosed as a case of periurethral stone with urinary incontinence due to urethro-vaginal fistula. Our surgical team successfully removed the stone formed by the encrustation of the displaced tape and repaired the fistula. Following the MVT, a high degree of suspicion and long-term follow-up is mandatory for the diagnosis and management of these rare complications. Highlights: Mini vaginal tape (MVT), a form of synthetic mid-urethral sling is popular for treating stress urinary incontinence. There are limited reports on periurethral stone formation and urethrovaginal fistula by MVT as it is rare. This study presents a case of periurethral stone in the MVT with urinary incontinence due to urethrovaginal fistula. Although rare, a high degree of suspicion is mandatory for the diagnosis and management of these rare complications.